Prevalence and comorbidities of autism among children referred to the outpatient clinics for neurodevelopmental disorders - Mpaka, Davin Mbeya; E-Andjafono, Daniel Luwa; Ndjukendi, Ally Omba; Mankubu N’situ, Adelin; Kinsala, Sebastien Yabassi; Mukau, Joachim Ebwel; Ngoma, Valentin Malanda; Kashala-Abotenes, Esperance; Ma-Miezi-Mampunza, Samuel; Vogels, Annick; Steyaert, Jeans (The Pan African medical journal, 2016)
Autism spectrum disorders (ASD) is a neurodevelopmental disorder that has been rarely diagnosed in Sub-Saharan Africa. Although a proportion of children do present features of ASD in the Democratic Republic of Congo (DRC), little is known about it prevalence. Often, the co-morbidities constitute the upfront symptoms and therefore may it recognition and management difficult, aggravating as such the prognosis. The present study therefore aimed at studying the clinical profile of autism spectrum disorder (ASD) and the associated morbidities among children and adolescents in outpatient clinics in Kinshasa, the Democratic Republic of Congo. We conducted a cross sectional study in the three outpatients centers receiving patients referred for neurodevelopmental disorders in Kinshasa, DRC, from June 2008 to June 2010. A total of 450 subjects aged from 1-18 years old were referred and included in the study. The clinical diagnosis for ASD was made using the DSM-IV-R and the ADIR. Co-morbidities were identified using DSM-IV-R criteria together with an extensive clinical interview and observation. All patients were subject to an intellectual quotient evaluation and an electroencephalogram reporting. Of the 450 subjects referred, 120 (29.3%) received the diagnosis of ASD, with boys outnumbering girls (OR 3:1. The mean age was 7.9 years (SD 3.4) (p< 0.001). Intellectual disability (75.83 %) and epilepsy (72.50%) were the main co-morbidities significantly associated with autism (p< 0.001). It was also found that co-morbidities were most frequent in subjects with an IQ<70 (p=0.05). ASD is frequent among patients referred for neurodevelopmental disorders in the three outpatients' centers for neurodevelopmental disorders in Kinshasa. Males seem to be more affected than female. The main co-morbidities were epilepsy and intellectual disabilities. Our findings suggest that it is important to screen for ASD and co-morbidities among all subjects referred for neurodevelopmental disorders and to undertake survey on ASD in various structures of rejected children from the society in Kinshasa DRC. This will help to identify and manage ASD and associated co-morbidities at an early stage for a better prognosis.